Acute whole-body vibration as a recovery strategy did not alter the content of gluteus medius monocarboxylate-transporters, lactatemia, and acidosis induced by intense exercise in horses - Carvalho, Júlia Ribeiro Garcia [UNESP]; Sales, Nathali Adrielli Agassi [UNESP]; Littiere, Thayssa Oliveira [UNESP]; Costa, Guilherme Barbosa [UNESP]; Castro, Catarina Mariano [UNESP]; Polisel, Emanuel Elias Camolese; Orsi, Juan Bordon; Ramos, Gabriel Vieira [UNESP]; Santos, Ivan Felismino Charas; Gobatto, Claudio Alexandre; Manchado-Gobatto, Fúlvia Barros; Ferraz, Guilherme Camargo [UNESP] (Frontiers, 2025)
Introduction: Several studies have explored alternatives to enhance the performance, health, and safety of sports horses. One promising method involves the use of vibrating platforms (VP), which offer passive exercise stimulation via mechanical oscillations distributed throughout the body. This type of exercise is referred to as whole-body vibration (WBV) and is an emerging strategy for accelerating muscle recovery. This study examined the dynamics of proteins responsible for transporting monocarboxylates (MCT1 and MCT4), and their relationship with lactatemia and acid-base balance in connection with WBV recovery following intense treadmill exercise in horses. Methods: Eight crossbred horses underwent the standardized exercise test on the treadmill to determine the velocity corresponding to the lactate threshold. This velocity was used to prescribe the external load of the acute intense exercise bout (AIEB), which was performed to recruit rapidly fatigable type II muscle fibers and induce hyperlactatemia and metabolic acidosis. The horses were assigned to three experimental groups in a crossover design, with a 7-day washout period. The treadmill group (TG) actively recovered through low-intensity treadmill walking. The WBV group (WBVG) followed a stepwise recovery protocol on VP, with each step lasting 2 min and the frequencies decreasing in a specific order: 76, 66, 55, 46, and 32 Hz. The sham group (SG) was designated for horses with the VP turned off. All groups experienced a uniform recovery strategy duration of 10 min. Heart rate (HR), rectal temperature (RT), lactatemia, glycemia, acid-base status and electrolytes, strong ion difference (SID), and muscle monocarboxylate transporters (MCT1 and MCT4), were assessed. Results: AIEB induced positive chronotropic effects, hyperlactatemia and moderate metabolic acidosis in all experimental groups. All groups also showed transitory hyperthermia, hyperglycemia, hypernatremia, hyperchloremia, hyperkalemia and SID reduction. HR was higher in TG than in the WBVG and SG immediately after the recovery procedures. Between the groups, there was no change in RT, lactatemia, glycemia and MCT1 and MCT4 content. Regardless of groups, the MCT4 content decreased 3 and 6 h after recovery strategies. Discussion: It was concluded that a single whole-body vibration session did not enhance recovery of lactatemia or acid-base balance in horses after intense treadmill exercise.